Exprorasi Metode Pengobatan Tradisional Oleh Para Pengobat Tradisional Di Wilayah Karesidenan Surakarta - Indarto Indarto; Agus Kirwanto (Interest : Jurnal Ilmu Kesehatan, 2018)
Abstract: Traditional Medicine Method, Treatment Method, Traditional Medicinal Herb Type, Plant Type. The empirical traditional medicine (battra) using herbs and physical skills to date is still in demand by the people in the Surakarta Residency area, reflected the increasing number of traditional healers who are currently performing traditional health practices, since they have been protected by Law no. 36 of 2014, which regulates the health of personnel, in article 11, paragraph 13, classifies traditional empirical health workers consisting of traditional herbal medicine and traditional health skills. It makes public confidence is still high with traditional medicine therefore need to be disclosed about the phenomenon of methods of traditional healers in the treatment of the community. The purpose of this study is to find out how batras perform detection of patient diseases, to know the method of treatment performed battra in treating patients, know the composition of the herb used for the treatment and know what medicinal plants used to treat patients. Qualitative research type with an explorative approach design with data collection method of indepth interviews and observation of 18 informants, using triangulation method, source and theory as test of data validity. The results of the study that battra use various ways to detect the patient's illness is bengan ask a complaint, history of the disease as well as menfatkan diognosa doctors are known from patients and check using aids such as reflection equipment, tensimeter, digital cameras and laptops to check iridology. there are 2 methods used battra treat the patient that is using herb/ herbal concoction and physical skill, among others cupping of reflexology, rukyah and therapy energi.didapatkan 23 type of concoction used to treat patient, and 81 medicinal plants used for patient's herb treatment.